Human rights and non human entities: a few thoughts on corporations - Laukyte, Migle (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
The paper focuses on the question whether the human rights could be ascribed to non human persons, and in particular, to corporations. This question is analyzed by (a) exploring the link between human rights and corporations through the freedom to conduct a business as a fundamental right, by (b) looking into the process of corporate humanization” carried out in the courts, and by (c) explaining how ascribing human rights to non humans does not necessarily mean lessen the position of human beings.